2024
DOI: 10.3390/jpm14030236
|View full text |Cite
|
Sign up to set email alerts
|

Age Is a Predictor of In-Hospital Outcomes for Left Ventricular Assist Device Implantation: A Nationwide Analysis

Abdul Rahman Akkawi,
Akira Yamaguchi,
Junichi Shimamura
et al.

Abstract: The 2018 heart allocation system has significantly influenced heart transplantation and left ventricular assist device (LVAD) utilization. Our study aims to investigate age-related outcomes following LVAD implantation in the post-allocation era. Using the National Inpatient Sample, we analyzed data from 7375 patients who underwent LVAD implantation between 2019 and 2020. The primary endpoint was in-hospital mortality following LVAD implantation, stratified by age categories. The age groups were 18–49, 50–59, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Finally, psychosocial factors like ongoing substance abuse, inability to provide informed consent, non-adherence to medical regimens, inability to maintain the VAD, and active mental illness or psychosocial instability also disqualify patients from VAD implantation (Feldman et al, 2013). Akkawi et al, 2024 suggested that patients aged 18-59 had lower in-hospital mortality rates (6-7%) compared to those aged 60-69 (12%) and over 70 (17%). Older patients faced higher risks due to more comorbidities, as indicated by the Charlson Comorbidity Index.…”
Section: Survival Rate Complications and Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, psychosocial factors like ongoing substance abuse, inability to provide informed consent, non-adherence to medical regimens, inability to maintain the VAD, and active mental illness or psychosocial instability also disqualify patients from VAD implantation (Feldman et al, 2013). Akkawi et al, 2024 suggested that patients aged 18-59 had lower in-hospital mortality rates (6-7%) compared to those aged 60-69 (12%) and over 70 (17%). Older patients faced higher risks due to more comorbidities, as indicated by the Charlson Comorbidity Index.…”
Section: Survival Rate Complications and Adverse Eventsmentioning
confidence: 99%
“…Age should be a key factor in LVAD patient selection and care. (Akkawi et al, 2024). Hemodynamic assessments are right heart catheterization, precise gauge cardiac pressures and output, and identifying individuals with severe hemodynamics is crucial.…”
Section: Survival Rate Complications and Adverse Eventsmentioning
confidence: 99%